PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 UNTUK MENINGKATKAN PEMAHAMAN KONSEP PECAHAN PADA SISWA TUNA GRAHITA KELAS IV DI SLB BANJARSARI WETAN - Winduko, Fudak; Mochamad Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students with intellectual disabilities (tuna grahita) often encounter difficulties in grasping abstract concepts, such as fractions, due to their cognitive limitations and the necessity for specialized teaching approaches. Interactive and visually engaging learning media are critical in helping these students understand basic mathematical concepts effectively. This study developed an interactive learning medium using Articulate Storyline 3, focusing on introducing fractions, understanding their forms, and comparing fractions through colorful and visually engaging representations.The research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) alongside tests for validity and effectiveness. Participants included fourth-grade students with intellectual disabilities from a special education school (SLB) in Banjarsari Wetan, Madiun. Findings revealed that the learning media is both valid—based on assessments from subject matter and media experts—and effective in improving students' comprehension of fractions. The use of interactive visuals significantly increased student motivation and facilitated a deeper understanding of the concepts.This research contributes to the development of inclusive, technology-based learning tools and provides a reference for educators in creating appropriate educational resources for special needs students..